Epigenetic transcriptional gene silencing in Entamoeba histolytica: Insight into histone and chromatin modifications - Maya Huguenin (2018)
We have previously discovered a unique mechanism of epigenetic transcriptional gene silencing in the Entamoeba histolytica trophozoites of strain HM-1:IMSS that resulted in the persistent downregulation of the amoebapore A (ap-a) gene, and that could be successfully applied to silence other virulence genes (cpA5, lgl1). In order to understand how the silencing is maintained throughout generations, we analysed whether modifications occurred at the chromatin level. Chromatin immunoprecipitation assays were done with antibodies specific to the methylated lysine 4 of E. histolytica histone H3. When the genes were in a transcriptionally silent state, the methylation levels of H3K4 in their coding region were significantly reduced. In contrast, the levels of core histone H3 were consistently higher in the silenced genes. Controlled chromatin digestion with micrococcal nuclease was used to assess changes in nucleosome compaction. We found a significant resistance to digestion in the promoter region of the silenced ap-a and cpA5 genes as compared to the parental strain that expresses those genes. Our data lend further support to the idea that histone modifications and heterochromatin formations are at the basis of the transcriptional silencing of genes in E. histolytica. © 2009 Cambridge University Press.